2022
DOI: 10.2147/opth.s346291
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic Full-Field Stimulus Thresholds in Patients with Treatment-Naive Age-Related Macular Degeneration

Abstract: Purpose To evaluate retinal sensitivity using chromatic full-field stimulus thresholds (FST) in patients with treatment naive exudative age-related macular degeneration (e-ARMD) before and during the first intravitreal anti-vascular endothelial growth factor (anti-VEGF) treatment. Patients and Methods After general ophthalmological examinations to diagnose patients with e-ARMD the FST, the central foveal thickness (FCt) and the visual acuity were assessed in 20 eyes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This is consistent with the FST having been initially developed expressly for this low vision patient population [ 1 ]. Non-IRD populations in which FST has been performed includes diabetic retinopathy [ 41 , 44 ], age-related macular degeneration [ 1 , 45 ] and one study in only visually healthy controls [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the FST having been initially developed expressly for this low vision patient population [ 1 ]. Non-IRD populations in which FST has been performed includes diabetic retinopathy [ 41 , 44 ], age-related macular degeneration [ 1 , 45 ] and one study in only visually healthy controls [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…A white stimulus is produced by using a broadband white light with a colour temperature of 6500 K [ 29 , 31 , 36 ]. Short wavelength (blue) and long wavelength (including red) stimuli can be produced using a range of LEDs [ 1 , 2 , 5 , 27 , 30 , 34 , 35 , 50 ]. Short wavelength LEDs with wavelengths between 444 and 470 nm and longer wavelength LEDs with wavelengths between 538 and 670 nm have been used.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…The strategies chosen for FST balance speed and accessibility. A majority of studies report a 4–2 staircase thresholding [ 1 , 2 , 24 , 29 , 31 , 35 , 42 , 43 ], though the number of reversals or steps to final thresholding vary in the literature. Those that report the methodology in the literature may be unaware of commercial proprietary implementation of the thresholding algorithm and may be reporting the previously published method of a 4–2 staircase which may not the method implemented in proprietary software.…”
Section: Technical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Additionally, in cases other than IRD, attempts have been made to use FST as a diagnostic tool. 12 A survey of RP patients with RPE-65 mutations showed that FST is used to evaluate these patients in 36% of centers in Europe. 13 …”
Section: Introductionmentioning
confidence: 99%